Structural and hemodynamic analysis of Weaire-Phelan scaffolds made of Ti-alloy as bone replacement component: A preclinical investigation. - Jaideep Singh Bhardwaj; Souptick Chanda (PLoS ONE)
In recent years, additively manufactured metallic scaffolds have generated significant interest among researchers working in the field of bone tissue engineering and orthopaedic implants. Although such intricate, porous architectures are promising as bone substitutes, they need to be thoroughly tested for structural robustness as well as their capacity for bony integration. In this present work, we introduced and preclinically evaluated the biomechanical viability of Weaire-Phelan (WP) Ti-alloy scaffolds as bone replacement components. Two distinct groups of WP scaffolds, namely WPA and WPD, of varying porosities were examined for comparative assessment. Finite element (FE) analysis, computational fluid dynamics (CFD) and uniaxial compression tests were performed on 3D printed as-built scaffolds to comprehensively evaluate the structural, hemodynamic, fatigue and morphometric properties of the two groups. The mechanical performances of the WP scaffolds of 70%, 80% 90% porous group (relative density 0.3 and lower) were found to accord with the natural trabecular bone tissue. However, WPA scaffolds demonstrated slightly superior mechanical performances as compared to WPD scaffolds (22%- 63% greater compressive modulus depending on the porosity). On the other hand, WPD scaffolds showed improved hemodynamic properties thereby implying enhanced osteogenic potential. Moreover, the range of effective elastic moduli corresponding to the WP scaffolds was found to be in good agreement with that of the natural bone tissue. As such, these designs were categorized based on their suitability at different anatomical sites. The overall performance metrics of the WP scaffolds underscore its potential for improved osseointegration, structural conformities and greater capacity for customization with enhanced manufacturability.